Strategic Communication for Artificial Intelligence Adoption in Islamic Finance: Governance, Ethics, and Public Trust - Alan Munandar; Rino Febrianno Boer; Sarah Yunizka (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This study aims to examine how strategic communication can support the responsible adoption of Artificial Intelligence in Islamic financial institutions, ensuring that technological innovation remains ethically grounded, socially legitimate, and publicly trusted. Method: This study employs a structured qualitative literature review with thematic analysis by synthesizing scholarship on Artificial Intelligence in Islamic finance, Islamic banking transparency, shariah governance disclosure, explainable Artificial Intelligence, fintech trust, and Islamic ethical perspectives. Result: The findings show that Artificial Intelligence creates opportunities for compliance support, service modernization, institutional efficiency, and digital innovation, but also generates communication risks when institutions fail to explain how Artificial Intelligence systems operate, how decisions are reviewed, and how accountability is maintained. Implication: This study contributes to the literature by positioning strategic communication as a constitutive component of Artificial Intelligence governance across the planning, implementation, and evaluation stages of technological adoption in Islamic financial institutions. Originality or Novelty: This study provides a distinct theoretical contribution by shifting the focus of Artificial Intelligence adoption from purely technical capabilities to a communication-centered governance paradigm, conceptualizing strategic communication not as a post-hoc promotional activity but as an active structural mechanism that directly operationalizes Maqasid al-Shariah values throughout the technology deployment lifecycle.